FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN TUBERKULOSIS PADA ANAK (STUDI DI BALAI KESEHATAN PARU MASYARAKAT SEMARANG) - Ratih Amanda Puspitasari; Lintang Dian Saraswati; Retno Hestiningsih (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2015)
Mycobacterium tuberculosis is an acid-resistant bacterium that caused tuberculosis. The children can suffered tuberculosis by direct transmission of adult positive BTA patients. Analytic observational study design with the type of case control studies used in this study. Samples were pediatric patients from January 2013 until December 2014. The samples used purposive sampling method that consist of 68 samples cases and control samples. Data were obtained through interviews and direct observations then analyzed with Chi-Square method. The results of this study the majority of patients at the age of 3 years (51,7%), the majority were female (55,2%), already immunized BCG (82,6%), and moderate nutritional status (40,7%). Almost all patients have no contact with adult smear (64,5%). Home environment is already qualified population density (99,4%), level of humidity (99,4%), the presence of ventilation (75,6%), and the composition of the floor (100%). While the lighting levels are not qualified (99.5%). Most of the respondents are in the home environment family members who smoke (61.6%). Education of parents level largely completed high school (41,9%), relatively good knowledge about tuberculosis (98%), and almost a whole does not work just as housewives (89.5%) with family incomes above the minimum wage Semarang (53.4%). The results of Chi-Square test showed that there is a relationship between the gender of the child (OR=0,445;CI95% = 0,241-0,821) and the presence of smokers (OR=2.007;CI95% = 1.074-3.751) and the incidence of tuberculosis.